IMPLIKATUR KONVENSIONAL DALAM ACARA REPUBLIK SOSMED SEGMEN 4 (ROASTING) DI TRANS TV - Elan Halid; Fitri Handayani (Asosiasi dosen IDEBAHASA KEPRI, 2021)
The purpose of this study was to describe conventional implicatures in the Republic of Social Media Segment 4 (Roasting) on ​​Trans TV. The theories used in this study include: (a) the nature of pragmatics, (b) the nature of implicatures, (c) conventional implicatures, and (d) the Republic of Social Media program on Trans TV. This research used a descriptive method. Sources of data in this study were comics and guest stars in the Republik Sosmed program in segment 4 (Roasting) on ​​Trans TV. The results of this study include: (a) on the Republic of Social Media program segment 4 (roasting), there were 5 conventional implicature data, (b) on October 08, 2017 presented comic Ridwan Remin, there were 2 conventional implicature data, (c) on October 14, 2017 presented comic Ridwan Remin, there were 3 implicature data, (d) on October 15 2017 presenting comic Yuda Keling, there were 3 conventional implicature data, (e) on October 21 2017 presenting comics Tretan and Rizki, there was 1 conventional implicature data, (f) on October 22, 2017 presenting the comics Tretan and Coki, there were 2 conventional implicature data, (g) on ​​October 28, 2017 presenting, the comic Yuda Keling there was 1 conventional implicature data, and (h) on October 29, 2017 presenting the comic Yuda Keling, there were 3 conventional implicature data.